MODEL PENGENDALIAN GERUSAN DI SEKITAR ABUTMEN DENGAN PEMASANGAN GROUNDSILL DAN ABUTMEN BERSAYAP - Purwantoro, Didik (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT The main aim of this research is to get a control of scouring around the abutmen of bridge. Scour around the abutments must be controlled because it is the main damage cause of abutments and the hydraulic structures built in the river bed. This research was carried out using expermental method by standart teaching flume and steady-uniform flow in Hydraulic Laboratory Civil Department Yogyakarta State University.. The research is done in clear-water-Scour The abutment model were spillthrough type, wing-wall type, triangular type and semi circular type.The research result shows that the good performance of maximum scour depth around the abutment ocurred at wingwall abutment for 4b lenght is equal to 11 cm. Keywords : Scouring, Groundsill, Wingwall abutment